The effectiveness of reciprocal teaching as reading comprehension intervention: a systematic review - Ting Pick Dew; Suyansah Swanto; Vincent Pang (ResearchGate, 2021)
Background and Purpose: This paper presents a comprehensive review of the research on reading comprehension interventions for ESL learners. Although numerous reviews have reported the effectiveness of reciprocal teaching in improving reading outcomes, only few reviews focused on the use of these strategies in ESL contexts. Hence, this review identified, evaluated and synthesized relevant literature in search of the effectiveness of reciprocal teaching and the features that are associated with improved reading comprehension outcomes. Methodology: Guided by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), a thorough search was performed on five major databases using the search terms “reciprocal teaching” or “reciprocal reading” and “reading comprehension” or “text comprehension”. Findings: The comprehensive search resulted in a total of 18 articles. The analysis coded these articles into eight main themes with four main themes concentrated on the features of the reciprocal teaching interventions: (a) purposes, (b) learning environment, (c) comprehension-monitoring, and (d) scaffolding, and another four main themes on the outcomes of the interventions: (e) results, (f) comprehension outcome measures, (g) reading strategies, and (h) conceptual change. Contributions: Conclusively, reciprocal teaching fulfilled the key features of effective intervention as significant gains were mostly observed in the research using reciprocal teaching as intervention. The versatility of reciprocal teaching makes the technique adaptable to learners of varying backgrounds, ages and levels of education.